Comparative methylome analysis of ICF patients identifies heterochromatin loci that require ZBTB24, CDCA7 and HELLS for their methylated state. (12th April 2018) - Velasco, Guillaume; Grillo, Giacomo; Touleimat, Nizar; Ferry, Laure; Ivkovic, Ivana; Ribierre, Florence; Deleuze, Jean-François; Chantalat, Sophie; Picard, Capucine; Francastel, Claire
Abstract: Alterations of DNA methylation landscapes and machinery are a hallmark of many human diseases. A prominent case is the ICF syndrome, a rare autosomal recessive immunological/neurological disorder diagnosed by the loss of DNA methylation at (peri)centromeric repeats and its associated chromosomal instability. It is caused by mutations in the de novo DNA methyltransferase DNMT3B in about half of the patients (ICF1). In the remainder, the striking identification of mutations in factors devoid of DNA methyltransferase activity, ZBTB24 (ICF2), CDCA7 (ICF3) or HELLS (ICF4), raised key questions about common or distinguishing DNA methylation alterations downstream of these mutations and hence, about the functional link between the four factors. Here, we established the first comparative methylation profiling in ICF patients with all four genotypes and we provide evidence that, despite unifying hypomethylation of pericentromeric repeats and a few common loci, methylation profiling clearly distinguished ICF1 from ICF2, 3 and 4 patients. Using available genomic and epigenomic annotations to characterize regions prone to loss of DNA methylation downstream of ICF mutations, we found that ZBTB24, CDCA7 and HELLS mutations affect CpG-poor regions with heterochromatin features. Among these, we identified clusters of coding and non-coding genes mostly expressed in a monoallelic manner and implicated in neuronal development, consistent with the clinical spectrum of these patients' subgroups. Hence, beyond providing blood-based biomarkers of dysfunction of ICF factors, our comparative study unveiled new players to consider at certain heterochromatin regions of the human genome.